2013
DOI: 10.3126/njms.v2i2.8940
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study of the isthmus of the thyroid gland in Bangladeshi cadaver

Abstract: Background: The position and size of isthmus of thyroid vary greatly in humans, and sometimes it is absent. The present study was designed to find out the difference in isthmus of the thyroid gland of Bangladeshi people in relation to age and sex. Methods: The cross-sectional, descriptive study was performed in the Department of Anatomy, Dhaka Medical College, Dhaka, from January to December 2008, on 73 post mortem human thyroid gland collected from unclaimed dead bodies. Isthmus was found in 60 cases. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A study on surgical anatomy of the pyramidal lobe and its significance in thyroid surgery reported that the pyramidal lobe was found in 61% of the cases (15) . On the other hand, the incidence of the agenesis of the thyroid isthmus has been reported by various authors (2325) . Pastor et al claimed that agenesis of the thyroid isthmus is the complete and congenital absence of the thyroid isthmus and is rare in humans (24) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on surgical anatomy of the pyramidal lobe and its significance in thyroid surgery reported that the pyramidal lobe was found in 61% of the cases (15) . On the other hand, the incidence of the agenesis of the thyroid isthmus has been reported by various authors (2325) . Pastor et al claimed that agenesis of the thyroid isthmus is the complete and congenital absence of the thyroid isthmus and is rare in humans (24) .…”
Section: Introductionmentioning
confidence: 99%
“…In their study on anatomical variations of the thyroid gland, Ranade and colleagues reported a 33% incidence of agenesis of the isthmus. Also, a cadaveric study reported the incidence of the isthmus agenesis of the thyroid gland in Bangladesh as 82.2% (25) .…”
Section: Introductionmentioning
confidence: 99%